Comparison of The Application of Islamic Values in Kauman Village Semarang and Arab Village Sugihwaras Pekalongan - Fahmi Syarif Hidayat; Suzanna Ratih Sari (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2022)
Islam entered Indonesia through trade and acculturated with local culture. This cultural acculturation causes differences in the characteristics of each region. The ethnic differences between the two villages attracted researchers to take a deeper look at the Islamic values in the Kauman Village Semarang and Arab Village Sugihwaras Pekalongan. This study aims to find the application of Islamic values with different ethnic backgrounds. The research method used is qualitative-comparative by comparing the Kauman Village Semarang with Arab Village Sugihwaras Pekalongan. The results of the analysis show that both the Kauman Village Semerang and the Arab Village Sugihwras are areas that apply Islamic values. The first application of Islamic values, Hablumminallah, is establishing a mosque at the beginning of settlement construction with the intention of spreading Islamic teachings, the second is the application of Hablumminannas values, namely the concept of hijab in residential and the environment, the last is the application of Hablumminalalamin values, namely the implementation of the concept of sustainable settlements. The novelty in this study is the finding of greater tolerance and acceptance of the Arabs towards Chinese and Javanese ethnicities in Arab Village Sugihwaras compared to Kampung Kauman Semarang.